1985
DOI: 10.1575/1912/4360
|View full text |Cite
|
Sign up to set email alerts
|

Fallout nuclides in Atlantic and Pacific water columns : GEOSECS data

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…The data show no evidence of significant differences between the measured 239,240 Pu concentrations at the two dumpsites and those at the control stations. Our measured total 239,240 Pu concentrations in surface waters (mean = 4.6 ± 1.7 mBq m -3 ; range = 2.4 -6.2 mBq m -3 ) are similar to those reported in the early 1990s by Holm et al [8], but a factor of 13 lower than those measured in NE Atlantic waters during 1972 (GEOSECS programme) [9]. As seen in other oceans and S274 RADIOPROTECTION Figure 2.…”
Section: Resultssupporting
confidence: 85%
“…The data show no evidence of significant differences between the measured 239,240 Pu concentrations at the two dumpsites and those at the control stations. Our measured total 239,240 Pu concentrations in surface waters (mean = 4.6 ± 1.7 mBq m -3 ; range = 2.4 -6.2 mBq m -3 ) are similar to those reported in the early 1990s by Holm et al [8], but a factor of 13 lower than those measured in NE Atlantic waters during 1972 (GEOSECS programme) [9]. As seen in other oceans and S274 RADIOPROTECTION Figure 2.…”
Section: Resultssupporting
confidence: 85%
“…The 30% lower coral %Sr values during the winter could not be due to increased depth of the mixed Table 4 for comparison of actual values. layer and entrainment of lower '?$r waters, since 90Sr levels in the subsurface waters are the same or higher than those in surface waters (BOWEN et al, , 1974LIVINGSTON et al, 1985). There is prelimin~ evidence that this seasonal variation in 9oSr activity in corals is related to the position of the Loop Current.…”
Section: Oceanographic Considerationsmentioning
confidence: 96%
“…The reconstructed 239Pu concentration based on the measurement of 90Sr for the 1962 sampling period is therefore 0.05 Bq/m3. The concentration of 241Am is estimated to have been 0.009 Bq/m", using a 241Am/90Sr ratio of about 0.001 determined from the station of Livingston et al (1985). The RAIG estimates that the current concentration of 90Sr in the Chukchi Sea is about 1 Bq/m(l.9…”
Section: -33 Arctic Seas and Source Waters Of The Atlantic And Pacifmentioning
confidence: 98%
“…For example, the average concentrations of 24*Am, 137Cs, 239,240Pu, and 90Sr in seawater to a depth of 80 m at one location in the northern Pacific Ocean sampled by Livingston et al (1985) in 1973 were 0.004, 6.1, 0.012, and 3.5 Bq/m3, respectively. In a later study involving lX7Cs, 239,240Pu, and 90Sr in the central North Pacific, Nagaya and Nakamura (1984) reported that the average concentrations of those nuclides in surface waters of the 35" to 40" N latitudinal zone for the years 1980 and 1982 were 5.6, 0.038, and 4 Bq/m3.…”
Section: -33 Arctic Seas and Source Waters Of The Atlantic And Pacifmentioning
confidence: 99%
See 1 more Smart Citation